Static Analysis and Improved Design of the Overrunning Clutch of Smart Gas Meter Valve - Lü Lin; Yao Jin; Xiang Xiaohan; Tang Xu (Jixie chuandong)
By using the Hertz theory and the finite element analysis software named ANSYS Workbench,a static analysis is conducted for the overrunning clutch used in a new type of motor valve of the intelligent gas meter,and drum modification of the roller generatrix is conducted according to the analysis results. The improvement results show that the drum amount at 0. 010 mm,the maximum equivalent stress of roller decreased by 24% from 10. 3 MPa to 7. 8 MPa,so that the service life of overrunning clutch is improved. The improving design results could have a certain guiding significance on the working reliability and stability for the overrunning clutch.